2022
DOI: 10.3389/fpubh.2022.957721
|View full text |Cite
|
Sign up to set email alerts
|

Acceptance of COVID-19 vaccine and associated factors among health care workers at public hospitals in Eastern Ethiopia using the health belief model

Abstract: IntroductionAcceptance of vaccination among Health Care Workers is mandatory to lessen and curve the spread of transmission of COVID-19. Even though the Health Belief Model is one of the most widely used models for understanding vaccination behavior against COVID-19 disease, COVID-19 vaccine acceptance among Health Care Workers in Ethiopia was not adequately explored by using the Health Belief Model domains.PurposeThis study aimed to assess COVID-19 vaccine acceptance and associated factors among Health care w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
13
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 9 publications
(15 citation statements)
references
References 54 publications
2
13
0
Order By: Relevance
“…Those who perceived themselves to be at high risk of getting infected with COVID-19, those who perceived the COVID-19 vaccination to be beneficial, and those with high cues to action were significantly more likely to have received the COVID-19 vaccine in the univariable analysis. Similar findings were reported among HCWs in China [80] and Ethiopia [46] and among the general population in Malawi [81], Israel [82] and Bangladesh [79]. These findings provide an evidence-based formulation of vaccination strategies.…”
Section: Discussionsupporting
confidence: 82%
See 3 more Smart Citations
“…Those who perceived themselves to be at high risk of getting infected with COVID-19, those who perceived the COVID-19 vaccination to be beneficial, and those with high cues to action were significantly more likely to have received the COVID-19 vaccine in the univariable analysis. Similar findings were reported among HCWs in China [80] and Ethiopia [46] and among the general population in Malawi [81], Israel [82] and Bangladesh [79]. These findings provide an evidence-based formulation of vaccination strategies.…”
Section: Discussionsupporting
confidence: 82%
“…The HBM has widely been used in determining vaccination behavior, particularly COVID-19 vaccination. Most HBM constructs have significantly been associated with COVID-19 vaccine acceptance [46,76,78,79]. In this current study, five constructs of the HBM provided a framework for assessing determinants of COVID-19 vaccination uptake among HCWs.…”
Section: Discussionmentioning
confidence: 89%
See 2 more Smart Citations
“…Conversely, two other studies found acceptance rates of 70.0% [ 22 ] and 78.6% among HCWs in Ghana, exceeding the regional acceptance rate in Africa [ 38 ]. Key determinants of vaccine hesitancy among HCWs, particularly in developing countries included concerns about vaccine effectiveness [ 39 ], knowledge about the vaccine [ 40 , 41 ], attitude towards vaccination [ 35 , 42 , 43 ], and health belief model measures, including perceived susceptibility to and severity of COVID-19 infection [ 44 , 45 ], perceived barriers and benefits to vaccination [ 42 ], and cues to action [ 46 ]. Globally, perceived COVID-19 vaccine effectiveness among the general population ranged from 67.8% to 95.9%, and factors such as age, sex, level of education, and marital status significantly influenced individual perception of vaccine efficacy [ 47 ].…”
Section: Introductionmentioning
confidence: 99%